The Crafting Unforgettable Dining Moments: The Impact of Brand Love, Satisfaction, and Trust on Customer Experience - Prasetyo, Stephen Sugiarto; Berlianto, Margaretha Pink; Kho , Ardi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: The purpose of this research is to determine the influence of brand experience on brand love, brand satisfaction, and brand trust, the impact of brand satisfaction on brand love and brand trust, and the influence of brand satisfaction, brand love, and brand trust on brand loyalty. Methods: The research method used was descriptive quantitative with a sample of 160 people. The sampling technique used purposive sampling, using the criteria of individuals who had dined at XYZ restaurant in Jakarta. The data analysis technique uses SmartPLS SEM. Research Finding: This research found that brand experience has a positive effect on brand love, brand satisfaction, and brand trust; brand satisfaction affects brand trust, and brand love affects brand loyalty. Theoretical contribution/Originality: The contribution of this research to academics is that brand experience plays an essential role in brand love, and brand love plays an essential role in customer loyalty. Practitioner/Policy implication: This research contributes to business people in the restaurant industry, who believe there is still a need for a good customer experience amidst post-pandemic conditions and digitalization. Research limitation: Only researched XYZ restaurants in Jakarta